Prognostic impact of atrial fibrillation in patients with hypertrophic cardiomyopathy in a community-based Japanese cohort: results from Kochi RYOMA study. (25th November 2020) - Kubo, T; Sugiura, K; Ochi, Y; Takahashi, A; Baba, Y; Hirota, T; Yamasaki, N; Doi, Y.L; Kitaoka, H
Abstract: Background: The prognostic impact of atrial fibrillation (AF) in patients with hypertrophic cardiomyopathy (HCM) is not fully elucidated. Purpose: The aim of this study was to examine the prevalence and prognostic impact of AF in a prospectively assembled community-based HCM patient cohort in an aged Japanese community. Methods: In 2004, we established a cardiomyopathy registration network in Kochi Prefecture, Japan, consisting of 9 hospitals, and finally 293 patients with HCM were followed. Results: The ages at registration and at diagnosis were 63±14 and 56±16 years, respectively, and 197 patients (67%) were men. 86 patients (29%) showed AF. During follow-up period of 6.1±3.2 years, 44 patients died. In those patients, HCM-related deaths occurred in 23 patients with an annual mortality rate of 1.3%. Regarding HCM-related adverse events including HCM-related deaths, appropriate ICD discharge, heart failure admission and hospitalization for embolic events, a total of 77 cardiovascular events in 70 patients occurred. Multivariate analysis revealed that presence of AF, left ventricular (LV) outflow obstruction, NYHA functional class III, and lower LV fractional shortening at registration were significant predictors of these adverse events. During the follow-up period, additional 31 patients (11%) developed new-onset AF. Importantly, the incidence of HCM-related adverse events was significantly higher in patients with new AF observed from its onset compared with those with AF at registration (log-rank p=0.029) (Figure 1). Conclusions: In an unselected HCM registry in an aged Japanese community, presence of AF, particularly new-onset AF, was associated with unfavorable clinical outcomes. AF is not just a marker of the disease stage but an important trigger of HCM-related adverse events. Funding Acknowledgement: Type of funding source: None